Training and developing non-Irish workers: The perspectives of interested stakeholders. Issue 6 (4th July 2016) - Prendergast, Mary
Abstract : Purpose: This paper aims to explore the challenges facing Irish organisations in the training and development of non-Irish workers. It analyses the importance of fluency in the host country's language and the approach taken by organisations in relation to language training. In-depth semi-structured interviews provide significant insights for the policies and practices of multiple stakeholders. Design/methodology/approach: The empirical research comprised 33 in-depth interviews conducted with employers, employees, trade unions and regulatory bodies, and an objective content analysis provided insights into the challenges Irish organisations face in the training and development of non-Irish workers. Findings: The results indicate that Irish organisations are given little advice or support regarding the development of non-Irish workers. The study concludes that organisations should re-consider current approaches to cultural diversity training and development of these workers, prioritising the provision of English language training for these workers. The study maintains that an understanding of cultural differences is a vital component in the training of this cohort of workers. Research limitations/implications: Further research is required in this area. This could include an investigation into the levels of transfer of learning upon completion of training programmes for non-Irish workers, and an evaluation of the understanding of cultural learning styles among trainers. Practical implications: Learning and development (L&D) initiatives are dependent on English language supports, which will ultimately be central to the successful training and development of non-Irish workers, and provision of affordable high-quality English language classes is crucial. An understanding of cultural differences, diversity and inclusion is equally important if this cohort of workers is to thrive in an Irish working environment. Social implications: The government's role must be considered a priority, assisting organisations in relation to their strategies for L&D. Originality/value: There has been a paucity of research on the issue of L&D for migrant workers in an Irish context. This paper contributes to the discussion and provides guidelines for employers and opinions for policymakers.